2022
DOI: 10.31620/jccc.06.22/07
|View full text |Cite
|
Sign up to set email alerts
|

Using One-Stop E-Commerce Platforms for Baby Product Purchases: Insights on Generation Y in Malaysia

Abstract: This study focuses on technological and selected psychological factors predicting the use of one-stop e-commerce platforms among Generation Y parents in Malaysia to purchase baby products. These platforms offer great convenience for parents as they can purchase almost anything at any time on one platform. Nevertheless, purchasing baby products is different because parents often prefer to physically inspect baby products and directly interact with the sales representatives for clarifications and assurance. Henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It was also found that almost every activity was being conducted online first and foremost, before offline options to provide convenience in participation. Online social media platforms Line and YouTube were also found to be the most used among the elderly, important information to consider in online marketing (Ann, & Noor, 2022).Online media have also taken an important role in informing people of news, activities, and social changes. In trade, the use of online media has expanded the market with aims to increase efficiency and reduce the costs of doing business.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that almost every activity was being conducted online first and foremost, before offline options to provide convenience in participation. Online social media platforms Line and YouTube were also found to be the most used among the elderly, important information to consider in online marketing (Ann, & Noor, 2022).Online media have also taken an important role in informing people of news, activities, and social changes. In trade, the use of online media has expanded the market with aims to increase efficiency and reduce the costs of doing business.…”
Section: Introductionmentioning
confidence: 99%